(untitled) (Praxis Educativa, 2023)
In this article we investigate the teacher’s discomfort in relation to the educational policies implemented during the pandemic for secondary schools. We organized the analysis around three axes of conflict: 1) decision-making regarding educational policies, 2) the lack of resources to implement policies, 3) teacher working conditions. To do this, we worked on interviews with teachers from different provinces of Argentina, done with the Network for the Collaborative Study of Representations on the Pandemic in Argentina (ENCRESPA). In the investigation it is observed that educational policies are represented simultaneously as something imposed and as something to be questioned, reinvented or resisted.